(untitled) (Advances in Applied Mathematics and Mechanics, 2019)
The paper presents a study of the influence of the domain size and LBM collision models on fully developed turbulent channel flows. The results using spectral method show that a smaller domain size will increase the velocity fluctuations in the streamwise direction. And MRT-LBM with different collision models gives reliable results at least for low order flow statistics compared with those from spectral method and finite-difference method.